Targeting MicroRNA-125b Promotes Neurite Outgrowth but Represses Cell Apoptosis and Inflammation via Blocking PTGS2 and CDK5 in a FOXQ1-Dependent Way in Alzheimer Disease - Zhuang, Jingcong; Chen, Zhongjie; Cai, Pingping; Wang, Rong; Yang, Qingwei; Li, Longling; Yang, Huili; Zhu, Renjing (Frontiers in Cellular Neuroscience, 2020)
This study aimed to explore the molecular regulatory network among microRNA-125b (miR-125b), Forkhead box Q1 (FOXQ1), prostaglandin-endoperoxide synthase 2 (PTGS2) and cyclin dependent kinase 5 (CDK5), as well as their effects on cell apoptosis, neurite outgrowth and inflammation in Alzheimer's disease (AD). Rat embryo cerebral cortex neurons and nerve growth factor stimulated PC12 cells were insulted by Aβ1-42 to construct two AD cellular models. Negative control (NC) inhibitor, miR-125b inhibitor, NC siRNA, FOXQ1 siRNA, PTGS2 siRNA and CDK5 siRNA were transferred into the two AD cellular models alone or combined. Then cell apoptosis, neurite outgrowth, proinflammatory-cytokines, miR-125b, FOXQ1, PTGS2 and CDK5 expressions were detected. MiR-125b inhibition facilitated neurite outgrowth while suppressed cell apoptosis and proinflammatory-cytokines (tumor necrosis factor-α, interleukin-1β and interleukin-6), meanwhile, it upregulated FOXQ1 while downregulated PTGS2 and CDK5. Furthermore, FOXQ1 inhibition promoted cell apoptosis and proinflammatory-cytokines while repressed neurite outgrowth; PTGS2 inhibition achieved the opposite effects; CDK5 inhibition attenuated cell apoptosis, while it less affected neurite outgrowth and inflammation. Notably, FOXQ1 inhibition attenuated while PTGS2 inhibition elevated the effect of miR-125b inhibition on regulating neurite outgrowth, cell apoptosis and proinflammatory-cytokines. As for CDK5 inhibition, it enhanced the effect of miR-125b inhibition on regulating cell apoptosis, while less impacted the neurite outgrowth and proinflammatory-cytokines. Additionally, PTGS2 inhibition and CDK5 inhibition both reversed the effect of FOXQ1 inhibition on regulating cell apoptosis, neurite outgrowth and proinflammatory-cytokines. In conclusion, targeting miR-125b alleviates AD progression via blocking PTGS2 and CDK5 in a FOXQ1 dependent way.